(untitled) (Journal of Philosophy Culture and Political Science, 2019)
The article analyzes the impact of hope as a projection of the future on the content and specifics of the national mentality. The author explores the phenomenon of social hope as a means for the survival of the cultural-national community in the future. The research based on the comparative analysis and reconstruction of the influence of national ideas about the future on the formation of mentality. This phenomenon considered as a pre-understanding of future coexistence, which based on the renewing experience of successful social practice, reflected in the mental environment. In the article analyzes the formation of the temporal axis of social hope in the national mentality. Special attention paid to the distribution and migration of subjectivity in promising social relations. It is noted that the presence and quality of the «voice of the nation», which serves as a model for future development, plays an important role in the existence of social hope. The practical significance of the work results lies in the substantiation of the concept of social hope as a significant foundation for the projection of future in mentality. The research material can used for teaching courses «Ontology», «Axiology», and «Prediction of social processes». Key words: social hope, national mentality, future, subjectivity, cogitation, chronotope, frame, repeatability, cultural-national community.